A Model for the Spacing of Quicklime Pile to Treat High Water Content Loess. (31st July 2020) - Guo, Hong; Nan, Yalin; Guo, Rui; Fu, Jiangtao
Abstract : There has been a long history for foundation treatment by quicklime pile, but as for establishing a more precise model formula used by actual construction, further research is needed to be done at present. Therefore, how to quantitate the factors affecting pile spacing is of great reference value for both actual constructions and theoretical studies. Based on the reference formula for handling weak foundation by lime pile and the practical problems in the western region, mathematical model analysis method is used to get a new model for high water content loess foundation treatment after considering the factors such as pile expanding, construction method, piles arrangement, and calcium oxide content. In this model, pile spacing coefficient is created and the model formula for different construction methods and different pile arrangements is also given. As a result, the reference formula used in high water content loess is somewhat conservative. The new model is also verified to be rational by the actual works at the end of the paper.